2011
DOI: 10.1161/strokeaha.111.619510
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of In-Hospital Complications in Patients With Clipped Versus Coiled Ruptured Intracranial Aneurysms

Abstract: on behalf of the Investigators of the Registry of the Canadian Stroke NetworkBackground and Purpose-After aneurysmal subarachnoid hemorrhage (SAH), patients with clipped aneurysms have a higher incidence of neurocognitive deficits and seizures compared with patients with coiled aneurysms. It remains unknown if patients with clipped aneurysms also have a higher incidence of other in-hospital complications. Methods-We used data from the Registry of the Canadian Stroke Network on consecutive patients admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…These complications have been associated with worse functional outcomes in previous studies. [12][13][14] The lack of effect on functional outcome of endothelin receptor antagonists also can be explained by a lack of effect on the incidence of both vasospasm-related infarctions and any new cerebral infarctions. Whereas there is general consensus that vasospasm is associated with neurological deterioration, cerebral infarction, poor functional outcome, and case fatality after SAH, causal relationships are subject to discussion.…”
Section: Discussionmentioning
confidence: 99%
“…These complications have been associated with worse functional outcomes in previous studies. [12][13][14] The lack of effect on functional outcome of endothelin receptor antagonists also can be explained by a lack of effect on the incidence of both vasospasm-related infarctions and any new cerebral infarctions. Whereas there is general consensus that vasospasm is associated with neurological deterioration, cerebral infarction, poor functional outcome, and case fatality after SAH, causal relationships are subject to discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis of these published trials shows that the odds of poor outcome are higher after surgical treatment than after endovascular treatment, despite a higher early risk of rebleeding from the target aneurysm after coil embolization. Furthermore, subgroup analyses from these clinical trials have indicated that the risks of seizures, 11 delayed cerebral ischemia, 12 ischemic lesions on MR imaging, 13 and in-hospital complications 14 are lower after coil embolization than after surgical clip ligation. A subgroup analysis of patients enrolled in the ISAT also showed improved cognitive outcome after coilingcompared with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Nationwide In-Patient Sample of the United States from 2002 to 2008 showed a relative increase of 40% in the utilisation of coiling in aSAH [4]. Vergouwen et al [25] also reported an increase in the usage of coiling from 2002 to 2008 in aSAH patients for Ontario, Canada. Our hospitalisation rates of aSAH potentially underestimate the true incidence of aSAH, because the preclinical mortality of aSAH ranges from 11 to 12% [26,27].…”
Section: Discussionmentioning
confidence: 99%